Observed near‐surface flows under all tropical cyclone intensity levels using drifters in the northwestern Pacific. Issue 5 (9th May 2013) - Chang, Yu‐Chia; Chen, Guan‐Yu; Tseng, Ruo‐Shan; Centurioni, Luca R.; Chu, Peter C.
Abstract : [1] Data from drifters of the surface velocity program and tropical cyclones (TCs) of the Joint Typhoon Warning Center during 1985–2009 were analyzed to demonstrate strong currents under various storm intensities such as category‐4 to −5, category‐2 to −3, and tropical storm to category‐1 TCs in the northwestern Pacific. Current speeds over 2.0 m s −1 are observed under major TCs with the strongest mean currents to the right of the storm track. This study provides the characterization of the near‐surface velocity response to all recorded TCs, and agrees roughly with Geisler's theory (1970). Our observations also verify earlier modeling results of Price (1983). Key Points: The characterization of velocity to all storms is provided. The study roughly agrees with Geisler's theory. Our observations verify earlier modeling results of Price [1983].